Early evaluation of a next‐generation surgical system in robot‐assisted total laparoscopic hysterectomy: A prospective clinical cohort study. (21st July 2022) - Borse, Mahindra; Godbole, Girish; Kelkar, Dhananjay; Bahulikar, Madhavi; Dinneen, Eoin; Slack, Mark
Abstract: Introduction: This study aimed to demonstrate the safe and effective use of the Versius surgical system (CMR Surgical, Cambridge, UK) in robot‐assisted total laparoscopic hysterectomy. This surgical robot was developed iteratively with input from surgeons to improve surgical outcomes and end‐user experience. We report data from the gynecology cohort of an early clinical trial designed in broad alignment with IDEAL‐D (Idea, Development, Exploration, Assessment, Long‐term follow‐up – Devices) stage 2b (Exploration). Material and methods: The study is registered in the Indian clinical trials register (CTRI/2019/02/017872). Adult women requiring total hysterectomy who provided informed consent and met the eligibility criteria underwent procedures at one of three hospitals in India. Five surgeons performed robot‐assisted total laparoscopic hysterectomies using the device from March 2019 to September 2020. The primary endpoint was rate of unplanned conversion to conventional laparoscopic or open surgery. Adverse events were adjudicated by an independent clinical events committee using endoscope video recordings and clinical notes. Results: In total, 144 women underwent surgery (median age: 44 years [range: 28–78]; median body mass index 25.8 kg/m 2 [range: 14.3–47.8]). The rate of unplanned conversion to conventional laparoscopy was 2/144 (1.4%); neither conversion was device related. No surgery was converted to open. In total, 13 adverse events occurred among seven (4.9%) patients, comprising seven serious adverse events and six adverse events. One serious adverse event was deemed device‐related. Two patients were readmitted to hospital within 30 days; both made a full recovery. No patients died within 90 days of surgery. Conclusions: The device provides a safe and effective option for total laparoscopic hysterectomy; these findings support its continued implementation in larger patient cohorts and expansion in other major minimal access indications.